Nonlinear Static Stability of Stiffened Nanocomposite Plate s Subjected Various Types of Loads - Van Thanh, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 38 No 1DO - 10.25073/2588-1124/vnumap.4685, 2022)
This work deals with the nonlinear buckling and post-buckling of stiffened nanocomposite plates reinforced functionally graded carbon nanotubes (FG CNTRC) resting on elastic foundation in thermal environment. Obtained results showed that the properties of the nanocomposited plates embedded with single-walled carbon nanotubes are dependent on temperature and altered according to linear functions of the thickness. The governing equations are derived by the third-order shear deformation plate theory taking into account von Kármàn geometrical nonlinearity and solved by both the Airy’s stress function and Galerkin method. In numerical results, the influences of various types of distribution and volume fractions of carbon nanotubes, geometrical parameters, elastic foundations on the nonlinear buckling and post-buckling behaviour of stiffened FG-CNTC plates subjected mechanical, thermal loading and both are demonstrated. Keywords: Stiffened FG CNTRC plates; Buckling and Post buckling analysis; Third-order shear deformation theory; Thermal environment; Galerkin method This work deals with the nonlinear buckling and post-buckling of stiffened nanocomposite plates reinforced functionally graded carbon nanotubes (FG CNTRC) resting on elastic foundation in thermal environment. Obtained results showed that the properties of the nanocomposited plates embedded with single-walled carbon nanotubes are dependent on temperature and altered according to linear functions of the thickness. The governing equations are derived by the third-order shear deformation plate theory taking into account von Kármàn geometrical nonlinearity and solved by both the Airy’s stress function and Galerkin method. In numerical results, the influences of various types of distribution and volume fractions of carbon nanotubes, geometrical parameters, elastic foundations on the nonlinear buckling and post-buckling behaviour of stiffened FG-CNTC plates subjected mechanical, thermal loading and both are demonstrated.